Productive Zakat Model: Economic Empowerment for Post-COVID-19 Recovery in Indonesia - Moh. Musfiq Arifqi; Ayi Sofyan; Dewi Mayaningsih; Rizka Fitriyah (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
Indonesia's economic landscape has been significantly impacted by the COVID-19 pandemic, both at micro and macro levels. To address these challenges, it is imperative to implement optimal and sustainable financial management strategies. Given Indonesia's predominantly Muslim population, the development of an Islamic financial system, including the use of Zakat as a distribution instrument, holds great potential. As an obligation for Muslims, Zakat can be a highly productive means of addressing the country's economic challenges.     This study proposes a model for economic empowerment through productive Zakat to effectively address the impact of the COVID-19 pandemic on the Indonesian economy. The research methodology utilized a library research approach with descriptive qualitative methods. Data was meticulously collected from various sources including books, articles, journals, news, homepages, and other scientific references. The management of productive Zakat has great potential for contributing to the economic recovery of Indonesia after the COVID-19 pandemic. Productive Zakat involves an economic empowerment model that has personal and spiritual dimensions, and its impact on social life is significant. The management of productive Zakat is a support system for the better and sustainable development of Indonesia's economy.